Students Adjustment to College: Quantitative Study of Physical Education Students in 2023 - Arwin; Insanistyo, Bayu; Eko Nopiyanto, Yahya; Ibrahim; Sari Kardi, Ipa (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. Adaptation is very important for student development, especially in the academic field. This study aims to describe the level of ability of physical education students in adapting to the academic environment in 2023. Materials and Methods. Quantitative research methods were used to achieve the research objectives. A total of 54 physical education students were part of the research sample. The research data was accommodated using an instrument in the form of a questionnaire distributed online via a google form link. Quantitative data analysis using ideal standards and ideal mean values was used to determine the classification of student adaptability. Results. The results showed that 11 students had very high adaptability, 29 students had high ability, 13 students had moderate ability, 1 student had low ability, and no students had very low ability. Conclusions. Based on the results found, it can be concluded that the adaptability of Physical Education students is dominantly in the high category.